Effects of living near a new urban motorway on the travel behaviour of local residents in deprived areas: Evidence from a natural experimental study. (January 2017) - Foley, Louise; Prins, Richard; Crawford, Fiona; Sahlqvist, Shannon; Ogilvie, David; ,
Abstract: We evaluated the effects of a new motorway built through deprived neighbourhoods on travel behaviour in residents. This natural experiment comprised a longitudinal cohort (n=365) and two cross-sectional samples (baseline n=980; follow-up n=978) recruited in 2005 and 2013. Adults from one of three study areas - surrounding the new motorway (South), an existing motorway (East), or no motorway (North) - completed a previous day travel record. Adjusted two-part regression models examined associations between exposure and outcome. Compared to the North, cohort participants in the South were more likely to undertake travel by any mode (OR 2.1, 95% CI 1.0–4.2) at follow-up. Within the South study area, cohort participants living closer to a motorway junction were more likely to travel by any mode at follow-up (OR 4.7, 95% CI 1.1–19.7), and cross-sectional participants living closer were more likely to use a car at follow-up (OR 3.4, 95% CI 1.1–10.7), compared to those living further away. Overall, the new motorway appeared to promote travel and car use in those living nearby, but did not influence active travel. This may propagate socioeconomic inequalities in non-car owners.